The contribution of educational class in improving accuracy of cardiovascular risk prediction across European regions: The MORGAM Project Cohort Component. Issue 15 (1st May 2014) - Ferrario, Marco M; Veronesi, Giovanni; Chambless, Lloyd E; Tunstall-Pedoe, Hugh; Kuulasmaa, Kari; Salomaa, Veikko; Borglykke, Anders; Hart, Nigel; Söderberg, Stefan; Cesana, Giancarlo; ,
Abstract : Objective: To assess whether educational class, an index of socioeconomic position, improves the accuracy of the SCORE cardiovascular disease (CVD) risk prediction equation. Methods: In a pooled analysis of 68 455 40–64-year-old men and women, free from coronary heart disease at baseline, from 47 prospective population-based cohorts from Nordic countries (Finland, Denmark, Sweden), the UK (Northern Ireland, Scotland), Central Europe (France, Germany, Italy) and Eastern Europe (Lithuania, Poland) and Russia, we assessed improvements in discrimination and in risk classification (net reclassification improvement (NRI)) when education was added to models including the SCORE risk equation. Results: The lowest educational class was associated with higher CVD mortality in men (pooled age-adjusted HR=1.64, 95% CI 1.42 to 1.90) and women (HR=1.31, 1.02 to 1.68). In men, the HRs ranged from 1.3 (Central Europe) to 2.1 (Eastern Europe and Russia). After adjustment for the SCORE risk, the association remained statistically significant overall, in the UK and Eastern Europe and Russia. Education significantly improved discrimination in all European regions and classification in Nordic countries (clinical NRI=5.3%) and in Eastern Europe and Russia (NRI=24.7%). In women, after SCORE risk adjustment, the association was not statistically significant, but the reduced number of deaths plays a major role, and the addition of education led to improvements in discrimination and classification in the Nordic countries only. Conclusions: We recommend the inclusion of education in SCORE CVD risk equation in men, particularly in Nordic and East European countries, to improve social equity in primary prevention. Weaker evidence for women warrants the need for further investigations.